Cultural Guidelines for Commercial Production of Interiorscape Hedera - Jianjun Chen; Dennis B. McConnell; Kelly C. Everitt (EDIS)
This article is intended to describe common species and cultivars grown in the foliage plant industry, provide guidelines for their culture and interior use, and list physiological problems that may be encountered during production and interiorscape use. It is suggested that the potential invasiveness of this species be noted at the retail level and that buyers be advised to only use this plant where it cannot become a nuisance. This document is ENH 990, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date November 4, 2004. Revised May, 2005.